STUDY OF PRESCRIBING PATTERN OF ANTIMICROBIAL AGENTS IN MEDICINE INTENSIVE CARE UNIT OF A TERTIARY CARE HOSPITAL - BG, DUDHE; D, CHAKRAVORTY ASHISH; NN, MANKAR; HN, PISE (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to assess the current use of antimicrobial agents (AMAs) and to assess prescription writing as per the WHO guidelines in the medicine intensive care unit (MICU). Methods: The present study was conducted on admitted patients in MICU of a tertiary care hospital. The demographic and clinical treatment data of patients were collected in specially designed pro forma from the case record form. Results: Of 400 patients enrolled in the study, 55.50% were male and 44.50% were female. A common indication of AMAs use was infection (61.75%), symptomatic (21.50%), and prophylactic (10.50%) use. In 65% patients, antimicrobial therapy was considered to be rational. The majority of patients have good recovery (61%). Polypharmacy was seen in 89.75% of patients. The average number of drugs prescribed per patient was 8.84±2.55. 1.90±1.20 was average number of AMAs per patient. Commonest AMAs prescribed are ceftriaxone (27.64%), metronidazole, and amoxicillin+clavulanic acid. Conclusion: This study visibly highlights the practice of polypharmacy, low uses of generic drugs, high usage of antibiotic, and injection. Cephalosporins are the most prescribed AMAs in the ICUs. Remedy of this situation requires regulation, education, awareness, compliance with protocol, and guidelines of AMAs use.